2011
DOI: 10.1007/s00011-011-0308-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on inflammation: overview of molecular mechanisms

Abstract: Multiple mechanisms may be responsible for the association of smoking and inflammation, and the identification of potential therapeutic targets should guide future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(203 citation statements)
references
References 112 publications
10
187
4
2
Order By: Relevance
“…Smoking activates the NF-κB pathway, which induces transcription of genes involved in immune regulation. 46 As a result, acute smoking exposure results in a systemic inflammatory response indicated by higher levels of leukocytes (neutrophils and macrophages) which release proinflammatory mediators such as TNF-α, IL-6 and hsCRP. 18,[47][48][49][50] The association of smoking and inflammation is also supported by epidemiologic studies which demonstrated a positive association of cigarettes per day with hsCRP, white blood cell count, and fibrinogen in univariate analyses.…”
Section: Inflammationmentioning
confidence: 99%
“…Smoking activates the NF-κB pathway, which induces transcription of genes involved in immune regulation. 46 As a result, acute smoking exposure results in a systemic inflammatory response indicated by higher levels of leukocytes (neutrophils and macrophages) which release proinflammatory mediators such as TNF-α, IL-6 and hsCRP. 18,[47][48][49][50] The association of smoking and inflammation is also supported by epidemiologic studies which demonstrated a positive association of cigarettes per day with hsCRP, white blood cell count, and fibrinogen in univariate analyses.…”
Section: Inflammationmentioning
confidence: 99%
“…The impact of smoking is not identical on different immune cells, and the adverse effect can be summarized as follows: inflammatory cells are recruited into the lungs but weaken the ability of those cells, and cell populations of some subtypes decrease and switch the immune response to a more harmful pattern. 7 On the other hand, immune cells play an important role in shaping the tumor microenvironment, which interacts with the tumor cells and can be involved in carcinogenesis, development, invasion, and metastasis of tumors. 8 Some antibody-based anticancer drugs that target immune-related receptors improve patients’ survival time to some extent, for example, ipilimumab targets cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), and nivolumab and lambrolizumab target the Programmed Death 1 (PD1) receptor and the PD1 ligand (PD-L1).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the molecular mechanism at least partially responsible for immunomodulating capabilities of smoking involves activation of inhibitor of IκB kinase (IKK), fosforylation of IκB (inhibitor of nuclear factor NF-κB), NF-κB nuclear translocation and histone acetylation (17,18,28). NF-κB is a key transcription factor regulating the expression of various proinflammatory cytokines and numerous studies have linked its activation to elevated cytokine expression in smokers (29). 20 other transcriptional factors regulated by smoking have been identified so far, including GATA, PAX5, Smad 3/4, AP-1, ISRE, ICSBP (30,31).…”
Section: Discussionmentioning
confidence: 99%